The history, current state and prospects of development of hotel business - Razumei, Yana; Chala, Kateryna (My University, 2015)
Hospitality is one of the main components of the tourism industry. Creation hotel is connected with the history of the need for travel and trips that were made by people.
Keywords: tourism industry; hotel; hospitality; індустрія туризму; гостинність; готель; индустрия туризма; отель; гостеприимство; кафедра іноземних мов професійного спрямування